Ultimate bending capacities of steel pipelines under combined loadings. Issue 4 (April 2016) - Wang, Hui-Ping; Li, Xin; Zhou, Jing
This article derives analytical solutions for steel pipelines subjected to combined bending moments, axial forces, and internal pressure by considering the effect of ovalization on the plastic region. Both lower and upper bound solutions are proposed based on the selection of a general modulus of pipe material. The ultimate bending capacity, as well as the moment–curvature relationship, can be obtained from the analytical solutions. A comparison of the analytical solutions with the experimental and numerical results finds the bending capacities and the moment–curvature curves in good agreement. Therefore, the proposed analytical solutions can be used to study the behavior of steel pipelines subjected to combined loadings.